Evaluation of Hole Performance and Force Magnitude on Drilling Parameter for Orthopaedic Surgical Bone Drilling / Noorazizi Mohamad Samsuddin ...[et al.] - Mohamad Samsuddin, Noorazizi; Izamshah, Raja; Kasim, Mohd Shahir; Che Haron, Che Hassan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Internal fixation of bone fractures using immobilization screws and plate is a common procedure in orthopaedic surgery. This surgical procedure involved drilling process into bone and fixative component'sinteraction, which create several problems. Few of the common problems associated in the bone drilling process are hole's accuracy, drill wanders and excessive heat generation, which was directly related to the drilling parameters. This paper investigates the effect of drilling parameter namely spindle speed and feed rate on the cutting force and hole performances namely suraface roughness and surface morphology. Designs of Experiment (DOE) historical data of Response Surface Method (RSM) were adopted to evaluate the correlation between the cutting parameter and the hole's performance. From the conducted investigation, it was found that the most dominant factor that affects the holes performance was spindle speed followed by the feed rate. In addition, the interaction between feed rate and spindle speed also controlled the hole's performances.